Studi Kasus: Gambaran Onset Blok Motorik pada Pasien Bedah Urologi dengan Spinal Anestesi di Rsud Dr. H. Moch Ansari Saleh Banjarmasin - Nike Aprilia Putri; Hanura Aprilia; Evy Noorhasanah (Lembaga Pengembangan Kinerja Dosen, 2026)
Spinal anesthesia is widely used in urological surgery because it provides effective sensory and motor blockade of the lower extremities. Motor block onset, defined as the interval between intrathecal anesthetic administration and the development of motor blockade, is an important indicator of anesthetic effectiveness. This study aimed to describe patient characteristics, motor block onset time, and the degree of motor blockade based on the Bromage Scale in patients undergoing urological surgery. A descriptive case study was conducted on five patients who received spinal anesthesia at Dr. H. Moch. Ansari Saleh Regional Hospital, Banjarmasin. Data were collected through direct observation of patient characteristics, motor block onset, and Bromage Scale scores. All patients were adults aged 18 years or older, consisting of one male and four females, with body mass index categories ranging from normal weight to obesity class II. Motor block onset varied between 1 and 7 minutes. Despite this variation, all patients achieved complete motor blockade with a Bromage Score of 3. The findings indicate that motor block onset differs among individuals, while complete motor blockade can still be achieved consistently, providing useful clinical information for evaluating the effectiveness of spinal anesthesia in urological surgery.